Analisis Pengaruh Volume Kendaraan Terhadap Tingkat Kerusakan Jalan Dengan Metode Bina Marga - Palilati, Mifidyah Putri; Bumulo, Nasir; Nento, Sartan; Ma’sum, Ratna Dwi; Marjun, Harmain (Innovative: Journal Of Social Science Research, 2024)
Abstract Roads are one of the important infrastructure that is needed in a region's transportation system. This research aims to identify damage that occurs on road pavement. The analysis method uses the Bina Marga method. The Bina Marga Method is a method of assessing road pavement conditions by visually surveying the condition of the road pavement. This method carried out a 12 hour field survey in Buladu Village, Gorontalo City, Jalan Rambutan District. West City, from Monday to Sunday.   The research results show that the road damage found on the Jalan Rambutan road section is the most dominant type of road damage, namely the type of crocodile crack damage of 7 m². With calculation analysis using the Bina Marga method, the Priority Order value is 6 based on table 1. This value is included in the Order category. Priority >6. In this category, the road is included in the periodic maintenance program. Keyword: Road, Road Damege,Traffic volume